Ein neuer Fall von Ophthalmomyiasis, hervorgerufen durch Oestrus ovis L. - Scherf, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1960)
There is reported and described a new case of human ophthalmomyiasis caused by 11 primary larvae of Oestrus ovis L.